Unreleased Bursts of Final Stops in English Words as Pronounced by Native Speakers of Javanese from Yogyakarta - Muhammad Furqon Abrori; Aris Munandar (Lexicon, 2020)
This research aims to describe how native speakers of Javanese from Yogyakarta realize final stops in English words, understand how often they pronounce final stops in English words with audible release burst, and examine whether release burst in final stops is a feature of Yogyakartan Javanese accent of English, based on their occurrence frequency. 20 native Javanese speakers from Yogyakarta were asked to pronounce 24 English words ending in stops: /p/, /t/, /k/, /b/, /d/, and /g/. The recordings were then analyzed and compared against recordings of the words produced by native English speakers using Praat to identify the release bursts. The finding shows that release burst can be found in 7 out of 80 (8.75%) recordings of words ending in final /p/, 8 out of 80 (10%) recordings of words ending in final /t/, 15 out of 80 (18.75%) recordings of words ending in final /k/, 10 out of 80 (12.5%) recordings of words ending in final /b/, 9 out of 80 (11.25%) recordings of words ending in final /d/, and 16 out of 80 (20%) recordings of words ending in final /g/. In total, 165 out of 480 (13.54%) recordings contain release bursts in the final stop.